The Effect of Boiling Time on Polyphenol Compounds and Antioxidant Activity of Ciplukan (Physalis Angulata .L) - Tuty Anggraini; Busra Al-Hafit; Netty Sri Indeswari; Daimon Syukri (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2021)
This study aimed to determine the effect of boiling time on polyphenol compounds and antioxidant activity ciplukan (leaves, stems, fruit, roots and mixture of each plant part). This research used Randomized Block Design (RBD) with five groups (leaves, stems, fruit, roots, and mixture of each part of the plant ) and three treatments (10, 20 and 30 minutes). The analysis for the experiment were the antioxidant activity of each part of the plant by using various incubation time, the antioxidant activity and total polyphenol for each treatment. The results showed that the duration of boiling had a significant effect on total polyphenols but no significant effect on antioxidant activity. The highest total polyphenols were obtained on leaves with 30 min boiling duration (1210.5 mg GAE / g), and the highest antioxidant activity was also obtained on leaves with 30 min boiling time (88.32%).